Integrating Lean Six Sigma and Industry 4.0 to Enhance Manufacturing Productivity in India - Navneet Kumar; Sachin Saini (Indonesia Academia Research Society, 2025)
Small and medium-scale manufacturing enterprises (SMEs) in India face increasing competitive pressure due to rising material costs, stringent quality standards, and limited operational resources. Enhancing productivity while maintaining cost efficiency and delivery reliability remains a significant challenge. This study investigates the impact of integrating Lean Six Sigma (LSS), Total Productive Maintenance (TPM), selective Industry 4.0 technologies, and energy management practices to improve manufacturing performance in an Indian transformer manufacturing SME. Using a structured case study approach, the research implemented a phased Operational Excellence (OPEX) framework over a six-month period. Value Stream Mapping identified process bottlenecks and excessive non-value-added time, while Six Sigma tools addressed quality variation in the coil winding process. TPM initiatives improved equipment reliability, and a low-cost IoT vibration sensor enabled predictive maintenance. Additionally, an energy audit guided targeted efficiency improvements. The results demonstrate substantial performance gains: production lead time decreased by 28.6% (from 28 to 20 days), coil winding defects were reduced by 60% (from 8.5% to 3.4%), on-time delivery improved from 55% to 85%, Overall Equipment Effectiveness increased by 35% (from 52% to 70.2%), and energy cost per unit declined by 20%. The findings confirm that a pragmatic, integrated OPEX framework can deliver multidimensional productivity gains without requiring large-scale capital investment. This study contributes to the manufacturing and operations management literature by providing empirical evidence that selective Industry 4.0 adoption can effectively complement Lean Six Sigma in SME environments, offering a scalable pathway to sustainable, digitally enabled manufacturing excellence.